Please answer ASAP! 100 points!
Simplify the expression: (2x-3y)^2/(3y-2x)^2
![Please answer ASAP 100 points Simplify the expression 2x3y23y2x2 class=](https://us-static.z-dn.net/files/da3/a94ad6ef212c533ff5f236f1997c8ca1.jpg)
Answer:
[tex]\large\boxed{\dfrac{(2x-3y)^2}{(3y-2x)^2}=1}[/tex]
Step-by-step explanation:
[tex]\dfrac{(2x-3y)^2}{(3y-2x)^2}=\dfrac{(2x-3y)^2}{\left(-1(2x-3y)\right)^2}\qquad\text{use}\ (ab)^n=a^nb^n\\\\=\dfrac{(2x-3y)^2}{(-1)^2(2x-3y)^2}=\dfrac{(2x-3y)^2}{1(2x-3y)^2}=\dfrac{(2x-3y)^2}{(2x-3y)^2}=1[/tex]